2016
DOI: 10.5194/isprs-annals-iii-3-27-2016
|View full text |Cite
|
Sign up to set email alerts
|

Rectification and Robust Matching Using Oriented Image Triplets for Minimally Invasive Surgery

Abstract: ABSTRACT:Stereo endoscopes for minimally invasive surgery have been available on the market for several years and are well established in some areas. In practice, they offer a stereoscopic view to the surgeon but are not yet intended for 3D measurements. However, using current knowledge about the camera system and the difficult conditions in object space, it is possible to reconstruct a highly accurate surface model of the current endoscopic view. In particular for medical interventions, a highly reliable poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…To improve matching results for applications having poor illumination conditions, a trinocular system which suppresses disturbing reflections is introduced. As described in Conen et al (2016), a dense point cloud from the observed surface is computed by a semi-global matching approach for three images. The presented trinocular system and the matching approach from Conen et al (2016) is used to evaluate the effect of polarising filters on image matching.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve matching results for applications having poor illumination conditions, a trinocular system which suppresses disturbing reflections is introduced. As described in Conen et al (2016), a dense point cloud from the observed surface is computed by a semi-global matching approach for three images. The presented trinocular system and the matching approach from Conen et al (2016) is used to evaluate the effect of polarising filters on image matching.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…As described in Conen et al (2016), a dense point cloud from the observed surface is computed by a semi-global matching approach for three images. The presented trinocular system and the matching approach from Conen et al (2016) is used to evaluate the effect of polarising filters on image matching. Therefore, two experiments on a moistened pig kidney are conducted (Figure 10).…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…To improve the reliability especially in regions with repetitive or low texture, a trinocular endoscope has been developed by Conen et al (2016). A third camera could easily be integrated into current stereo endoscopes and should bring a higher reliability and accuracy for surface reconstruction.…”
Section: Trinocularmentioning
confidence: 99%
“…The computational most expensive part is the semi-global optimisation which is applied once during the process using the aggregated NCC of a corresponding point triplet. A comprehensive description of the algorithm is given in Conen et al (2016).…”
Section: Figure 7 Miniaturised Cameras and Trinocular Mountingmentioning
confidence: 99%
See 1 more Smart Citation